A Rare Case Report of an Intradural Left Cerebellopontine Angle Chordoma - Hazra, Darpanarayan; Balasubramanian, Chandramouli; Das, Soutrik; Tiwari, Mona; Ghosh, Amit (Asian Journal of Neurosurgery, 2022)
Intracranial intradural chordomas are rare entities constituting 1 to 3% of primary bone tumors. The mainstay of treatment remains aggressive resection of the lesion followed by adjuvant radiation therapy. We hereby report a case of a 70-year-old gentleman with intracranial, intradural chordoma arising from the left cerebellopontine angle. We hope to add to the existing minimal literature on this subject by highlighting this case, the first reported one from Asia.
Keywords: CP angle tumor; petroclival chordoma; brachyury; chordoma; skull base tumor